Magneto-thermoelectric effects mapping using tip-induced temperature gradient in atomic force microscopy - Isshiki, Hironari; Budai, Nico; Otani, YoshiChika (Frontiers in Physics, 2023)
Mapping magneto-thermoelectric effects, such as the anomalous Nernst effect, are crucial to optimize devices that convert thermal energy to electric energy. In this article, we show the methodology to realize this based on a technique we recently established using atomic force microscopy, in which a tip contact on the surface locally creates the temperature gradient. We can map the non-magnetic Seebeck and anomalous Nernst effects separately by investigating the magnetic field dependence. The simulation based on a simple heat transfer model between the tip and sample qualitatively explains our results. We estimated the magnitude of the anomalous Nernst effect in permalloy from the experiment and simulation to be ~ 0.10 µV/K.